Prolapso rectal por Trichuris trichuria - Argueta, Magdiel (Escuela Universitaria de las Ciencias de la Salud, EUCS, UNAH-VS, 2015)
Acta Pediátrica Hondureña, Vol. 5, No. 1 y 2 / Abril 2014 a Marzo 2015: 370